MENGEMBANGKAN KEMAMPUAN DASAR MATEMATIKA SISWA BERDASARKAN NCTM MELALUI TUGAS TERSTRUKTUR DENGAN MENGGUNAKAN ICT (Developing The Basic Abilities of Mathematics Students Based on NCTM Through Structured Tasks Using ICT) - Hafriani Hafriani (Jurnal Ilmiah Didaktika, 2021)
National Council Of Teacher Of Mathematics (NCTM) said that learning Mathematics goals develop five basic abilities, namely problem solving, communication, connection, reasoning, and representation. These five abilities are essential to be considered and assured its accomplishment. Thus, developing these five abilities cannot be separated because they contribute to one another. While in fact, these five Mathematics abilities of students are still low. This research aimed to know the development of these five basic Mathematical abilities through structured tasks using the blog and explaining the importance of basic Mathematical skills in math learning and how Mathematics builds basic math skills to students. One of them is to implement a blog-assisted structured task method. This research sample was five classes from 11 class X MAN 1 Aceh Barat and 1st grade from 2nd grade X SMA Unggul Tunas Bangsa, Aceh Barat Daya selected with random sampling. The data collection instrument was a written test of the five basic Mathematical abilities and interviewing few students. The Data was analyzed using T-Test. The results of the analysis showed that not all basic abilities developed. From these five basic mathematical abilities, three basic Mathematical abilities developed, namely problem solving, connections, and communication. In comparison, the other two capabilities did not develop, namely reasoning and representation.